2017
DOI: 10.1039/c6ra26169h
|View full text |Cite
|
Sign up to set email alerts
|

The electronic properties of the stanene/MoS2 heterostructure under strain

Abstract: The effect of a MoS2 substrate on the structural and electronic properties of stanene were systematically investigated by first-principles calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…It has already been reported that even when the substrate belongs to the van der Waals type, it can also induce an external potential for silicene [4] and germanene [51], because of its unique buckling structure. Here we take h-BN as an example to illustrate the substrate effects on stanene [50][51][52][53]. We first consider 1×1 stanene (4.68 Å) on a 2×2 h-BN (5.02 Å) substrate with a 6.8% lattice mismatch 1 .…”
Section: Substrate Effectmentioning
confidence: 99%
“…It has already been reported that even when the substrate belongs to the van der Waals type, it can also induce an external potential for silicene [4] and germanene [51], because of its unique buckling structure. Here we take h-BN as an example to illustrate the substrate effects on stanene [50][51][52][53]. We first consider 1×1 stanene (4.68 Å) on a 2×2 h-BN (5.02 Å) substrate with a 6.8% lattice mismatch 1 .…”
Section: Substrate Effectmentioning
confidence: 99%
“…MoS 2 , WS 2 , MoSe 2 , WSe 2 , MoTe 2 ) sired level of electronic properties and in-plane as well as out-of-plane strengths. Besides intense research on different two-dimensional hexagonal nano-structural forms, recently the development of novel application-specific heterostructures has started receiving considerable attention from the scientific community due to the tremendous prospect of combining different single layer materials in intelligent and intuitive ways to achieve several such desired physical and chemical properties [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen from the figure, the bandgap of the two electronic structures is a direct bandgap, ReSe 2 is a semiconductor with a bandgap of 1.25 eV, but the bandgap of ReSeS is 1.32 eV, which is larger than that of ReSe 2 . And as shown as figures 2(a) and (c), we can see that the bottom of the conduction band is farther away from the Fermi surface [21]. In figures 2(b), (d) and (e), they are band structures of ReTeSe, ReTeS and ReTe 2.…”
Section: Resultsmentioning
confidence: 78%